Computational insights on the origin of enantioselectivity in reactions with diarylprolinol silyl ether catalysts via a radical pathway. Issue 14 (8th June 2022) - Lam, Ching Ching; Goodman, Jonathan M.
Abstract : The stereoselective reaction of 1, 4-dicarbonyls with diarylprolinol silyl ether catalysts was studied with force field and density functional theory calculations. Abstract : The stereoselective reaction of 1, 4-dicarbonyls with diarylprolinol silyl ether catalysts was studied with force field and density functional theory calculations. A robust procedure has been developed for computational investigations of large and flexible chemical systems based on the conformation labelling system, ONIOM calculations and Python scripting. The change in enantiomeric excess due to variations in the catalyst can be explained based on conformational changes and structural deformations. In the enantioselectivity-determining radical addition step, the iminium in the most stable SR transition state (TS) takes up the conformation of the most stable ground state iminium (EE). The conjugated iminium in the SS TS adopts an EZ conformation to avoid potential structural deformations due to radical attacks from the more sterically hindered position. For systems with simpler catalysts, the iminium is EE for both, as the steric hindrance imposed by the substituent is not sufficient to cause this large structural deformation, and so the reaction shows poor enantioselectivity.